(untitled) (PerCursos, 2025)
This article addresses the role of Social Cartography (CS) as a methodology that brings students closer to their reality, allowing them to construct a cartographic language that reflects their experiences and perspectives. The objective is to present CS as a language tool for geographic education, aimed at students of basic education, of the 4th year of elementary school and 1st year of high school, in the municipality of Baía Formosa/RN. The study follows the methodological path of CS, with different phases and procedures, resulting in the realization of two workshops at different times. The workshops culminated in the elaboration of participatory maps that reflect the vision of the participants, highlighting the role of the student as the protagonist of their own geographical experience. Therefore, the importance of CS as a pedagogical approach that promotes contextualized and meaningful learning is highlighted, enabling students and teachers to understand and represent the space in which they live in an authentic and reflective way, supported by pre-existing and well-known geographical contents.